Chemsitry Learning Outcomes of 11th Grade Science Students at SMAN 1 Rasau Jaya - Fitrianti, Nenny; Melati, Husna Amalya; Rasmawan, Rahmat; Sartika, Rody Putra; Hadi, Lukman (Universitas Pendidikan Mandalika, 2024)
This study discusses the ineffective chemistry learning process resulting in poor grades at State Senior High School (SMAN) 1 Rasau Jaya, students tend to receive information from the teacher without constructing their own knowledge, so students have difficulty in constructing the material obtained from the teacher. The purpose of this study is to describe the learning outcomes of students in 11th Grade Science Class odd semester in chemistry subjects at SMAN 1 Rasau Jaya. The form of research used in this research is descriptive research, and the type of research is a case study. Case study is one of qualitative research, in which researchers conduct in-depth exploration of programs, events, processes, activities, for one or more people. The subjects of this study were students of 11th Grade Science Class at SMAN 1 Rasau Jaya in the 2019/2020 school year who took the odd semester general test, totaling 93 students. The research process includes three stages, namely the preparation stage, the implementation stage, and the final stage. The data collection tool used is the odd semester general test score. Results and Discussion regarding Indicator 1: List the general formula of alkane, alkene and alkyne compounds, Indicator 2: Mention the law of conservation of energy, Indicator 3: Determine the number of moles from the results of the experiment, Indicator 4: Determine the value of the equilibrium constant Kc based on the reaction. The results of the general test conducted on 11th Grade students of SMAN 1 Rasau Jaya can be concluded that the learning outcomes of students in the class are not adequate.